The Level of Classroom Teacher Digital Literacy in the Technology Dimension of the Instant Digital Competence Assessment (IDCA) - Sajidan, Sajidan; Atmojo, Idam Ragil Widianto; Ardiansyah, Roy; Chumdari, Chumdari; Adi, Fadhil Purnama; Wulandari, Wulandari (Mimbar Sekolah Dasar, 2023)
This study aims to describe the level of digital literacy of elementary school teachers, especially in the technological dimension. Based on the Law of the Republic of Indonesia No. 14 of 2005 concerning Teachers and Lecturers, article 20 verse 2, teachers are required to be able to use technology. However, in reality, many teachers still have a low ability in using technology. The method used in this research is a descriptive qualitative method with a case study approach. The subjects in this study were teachers of grades 1 to 6 coming from six different elementary schools. The classroom teacher's digital literacy level was measured using a test technique. The results of the study showed that teachers of grade 1, grade 2, grade 3, and grade 4 had low digital literacy categories, while teachers of grade 5 had moderate digital literacy categories, and teachers of grade 6 had a very low category of digital literacy. Based on these results, it can be concluded that there is no equality in the digital literacy abilities of classroom teachers in elementary schools.